The Implementation of Inclusive Digital Learning Materials in the Education of Students with Special Needs: A Literature Review - Aqirully Ramadhani; Baiq Ziadatu Rahmah; Alya Rizkika (Indonesian Journal of Teacher Education, 2025)
Inclusive education is an effort to provide equal learning opportunities for all students, including those with special needs. Advances in digital technology offer opportunities to create learning materials that are more adaptive, flexible, and accessible to a wide range of students. This study aims to analyze the implementation of inclusive digital learning materials in education for students with special needs through a literature review. The method used is a Systematic Literature Review (SLR) analyzing 15 scientific articles published in national journals between 2015 and 2024. The findings indicate that the use of digital learning materials in inclusive education can enhance accessibility, interaction, and understanding of the material for students with special needs. More specifically, the use of Learning Management System (LMS)-based platforms, interactive media such as animations and educational videos, and adaptive e-learning applications has proven to be most effective in supporting flexible learning tailored to students’ individual needs. Additionally, features such as audio support, interactive visuals, and simple navigation play a crucial role in enhancing student engagement.